Identifying determinants of CSR implementation on SDG 17 partnerships for the goals - Rosalia G. Castillo-Villar (Cogent Business & Management, 2020)
The launch of the United Nations' Sustainable Development Goals (SDGs) has established a new paradigm in sustainable development, where cross-sector partnerships (CSP) take a central role with SDG 17 on partnerships for the goals. At the same time, the SDGs have recognized the essential role of the main social actors such as businesses, government, civil society, and universities working together to reach a sustainable development. However, the literature related to Industry-University collaboration remains underdeveloped. Moreover, Industry-University CSP in developing countries exhibits unique complexities. This paper proposes a quantitative methodology to identify the key dynamic determinants of the implementation of CSP between industry and university in the context of a developing country. The methodology involves non-parametric association and inferential statistical analysis to obtain the main determinants that lead to the implementation of these programs. A case study in a developing country was created and surveys of companies were collected and analyzed. The proposed methodology is transferable to different types of partnerships and other geographical contexts.
Keywords: 650; Corporate social responsibility; sustainable development goals; cross-sector partnerships; UN 2030 agenda; quantitative